(untitled) - Ellis, Peter Berresford (Hoboken, N.J., 2004)
The book covers more than twenty historical events covering three millennia in 300 pages.The book is well referenced and has a great bibliography. It includes many primary sources and eyewitness accounts.
Keywords: Ireland; Lịch sử